New taraxasterane-type triterpenes from Diaphragma juglandis Fructus. (22nd June 2022) - Tan, Jin-Yan; Cheng, Yan-Gang; Li, Jian-Li; Ren, Hai-Qin; Li, Hui; Huang, Yu-Rong; Qiao, Yuan-Biao; Li, Qing-Shan; Wang, Ying-Li
Graphical abstract: Highlights: Four new taraxasterane-type triterpenes were isolated from Diaphragma juglandis Fructus. The structures of juglansin A were determined by X-ray analysis. New taraxasterane-type triterpenes exhibited moderate α-glycosidase inhibitory activities. Abstract: Phytochemical investigation into the Diaphragma juglandis Fructus led to the isolation of four new taraxasterane-type triterpenes (1 –4 ). The structures of 1 –4 were elucidated by extensive analyses through HRESIMS, NMR and X-ray single-crystal diffraction analysis. In addition, the α-glycosidase inhibitory activities of 1 –4 were evaluated and further analysis by molecular docking experiments were adopted to reveal the structure-activity relationship.